Pemanfaatan aplikasi VN Untuk Pembuatan Video Pembelajaran Menggunakan Telepon Pintar Pada Guru PAUD/TK Gusus 3 Kota Mataram - Ardi, Raden Fanny Printi; Purmadi, Ary; Wibawa, Restu; Maulachela, Adam Bachtiar; Juliansyah, Akbar; Kumoro, Danang Tejo (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2021)
Covid-19 is a virus that makes the learning and teaching process unable to run properly. All activities that involve large numbers of people are advised not to be carried out to prevent the spread of the COVID-19 virus. This also has an impact on teaching and learning activities throughout Indonesia, including kindergarten/PAUD schools in the Cluster 3 area of ??Mataram City. Currently, teaching and learning activities are still carried out but using online methods. This situation makes teachers feel the need to improve their ability to deliver material through online-friendly learning media, as well as friendly to TK/PAUD students. The method used is a combination of online / offline that applies health protocols. Offline is carried out when providing theoretical training materials as well as during guidance and evaluation, while offline is carried out when carrying out practice and demonstrations. The whole process of community service is divided into three stages, namely preparation, implementation, and evaluation. The purpose of this service is to train TK/PAUD teachers in the Mataram City cluster 3 who do not have a scientific background in information technology and are required to carry out teaching and learning activities using online methods. The results of the evaluation of this training activity teachers are able to make learning videos using smart phone devices. So the teacher is no longer constrained when carrying out Teaching and Learning Activities with the online method